Vinte e três anos do Assentamento Palestina: posse da terra, sonhos, possibilidades e desafios - Chaves, James Lima (2022)
It was noticed that the spatialization of the Jiquiriçá Valley reflects the land inequalities verified in the history of Brazil, and it was in this scenario that the emergence of the first agrarian reform settlement of this identity territory took place, in 1998, as a result of the expropriation of the Palestine Farm, in Cravolândia-BA, resulting in lots that accommodated 180 families. However, after the conquest of the land, many social, environmental and economic challenges are presented to the beneficiary families. This situation worsens when the settlement is implemented in a semi-arid climate area without considering its limitations and potential. Thus, two decades after the creation of the Palestine Rural Settlement, this research aimed to diagnose the socio-environmental and economic dimensions in order to identify driving and limiting factors for the development of Social Technologies (TS). The work was characterized as an action research, therefore, multiple data collection techniques were selected to carry out the diagnosis: bibliographic survey, documentary research, participant observation, field diary and use of a Participatory Rural Diagnosis (DRP). To socialize the results, the Freirean culture circle was used. The DRP carried out, in direct contact with the settled small family farmers, highlighted deep social, economic and environmental problems aggravated by the lack of technical assistance, illiteracy, lack of adequate policies for the semiarid region, among other issues. Even in the face of all the limitations, the settlers' desire is to remain on the land and produce their existence, in this sense, the TS identified there prove to be favorable to the permanence of these people in the countryside and to Endogenous Local Development (DLE), as they value the local knowledge and endogenous resources. The Freirean culture circle made it possible to gather all the data collected to expose them to the sieve of collective reflection and dialogicity, in addition to providing the elaboration of an action plan for the identified problems. The work allowed accessing different ways of practicing agriculture, resisting and interacting with the natural, social and economic environment, and revealed the survival strategies of a population that daily faces the abandonment of the institutions that should assist it.